Anxiety & inhibition: dissociating the involvement of state and trait anxiety in inhibitory control deficits observed on the anti-saccade task. Issue 8 (16th November 2020) - Myles, Owen; Grafton, Ben; MacLeod, Colin
ABSTRACT: The existence of a relationship between heightened anxiety and impaired inhibitory control is well established. However, it remains unknown whether such reduced inhibitory control is a stable characteristic of elevated trait anxiety, is driven by elevated state anxiety, or is a joint function of both trait and state anxiety. The present study sought to resolve this issue, by having high and low trait anxious participants complete an anti-saccade task, following a manipulation of state anxiety level using a video-based state anxiety induction procedure. We found that impaired inhibitory control was interactively determined by trait and state anxiety. Specifically, in high but not low trait anxious participants, the induction of heightened state anxiety served to impair inhibitory control. In addition to shedding light on how inhibitory control may potentially contribute to dispositional anxiety, these findings suggest that the anxiolytic benefits of inhibitory control training procedures may be greatest when delivered to high trait anxious individuals during periods of elevated state anxiety.